Antibody tits: detection of swollen head syndrome using indirect ELISA test - Lies Pardede; Ngekep Ginting (Indonesian Center for Animal Research and Development (ICARD), 1995)
Indirect enzyme-linked inununosorbent assay (ELISA) was standardised using vaccine strain to detect antibody respons raised to swollen head syndrome (SHS) . This technique can be used as an alternative serologic test due to its quickness, simple and relatively cheap. Besides, it would be suitable as a preliminary test before using serum neutralisation test (SNT) for reassuring diagnosis which takes time and costly for developing poultry industries.